Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1109/tac.2019.2934393
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-Time Sliding-Mode Control With a Desired Switching Variable Generator

Abstract: This paper introduces a new, reference trajectory following, sliding-mode control strategy for disturbed discrete-time systems. The strategy uses an external trajectory generator based on a switching type reaching law. The trajectory following strategy not only ensures all the properties of the quasi-sliding-mode as defined by Gao et al., but with a certain choice of the control parameters it also guarantees a significant reduction of the quasisliding-mode band width and the errors of all the state variables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…Various works have appeared in the last years to fill the gap between the continuous and the discrete-time counterparts; see previous studies [28][29][30] just to cite a few. Nowadays, discrete-time SMC is popular among control engineers, as one can find in the literature many examples of applications in various fields of industrial interest [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Various works have appeared in the last years to fill the gap between the continuous and the discrete-time counterparts; see previous studies [28][29][30] just to cite a few. Nowadays, discrete-time SMC is popular among control engineers, as one can find in the literature many examples of applications in various fields of industrial interest [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…So, the elimination of the chattering phenomenon has attracted more and more attention recently. For example, adaptive sliding mode control [14,15], fuzzy sliding mode control [16], discrete-time sliding mode control [8,17], neural dynamic sliding mode control [18] and integral sliding mode control [19] have been proposed to mitigate the adverse effects of the chattering phenomenon. It has been reported that designing a continuous sliding mode control law to replace the discontinuous law, e.g., continuous TSMC (CTSMC) can reduce the impact of the chattering [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Sliding mode control (SMC) has been intensive focus on nonlinear systems, the main reasons are that the control method with sliding mode manifold is insensitive to parametric variations, increasing the robustness of controller in nonlinear systems. Given to the advantages, the SMC has been widely applied in complicate nonlinear systems to solve the tracking control problems, such as robotic systems, 1‐3 unmanned aerial vehicle (UAV) systems, 4,5 and power generator systems 6‐8 …”
Section: Introductionmentioning
confidence: 99%